Nuclear identities and Scottish independence. Issue 5 (1st November 2016) - Ritchie, Nick
ABSTRACT: This article argues that the study of national identity is central to understanding and explaining national and transnational nuclear politics. It argues that the meanings assigned to nuclear weapons are not fixed or self-evident, but are instead changeable and contingent on social and historical context. The article develops this argument by studying how the Scottish National Party has framed UK nuclear weapons in ways very different from those of the major UK political parties. It argues that the SNP has done this by developing and promoting a specific national identity for an independent Scotland in which nuclear weapons have no place. This identity is juxtaposed against that of a "Westminster other" for whom nuclear weapons remain highly valued. The article provides an original constructivist case study of contemporary Scottish-British nuclear politics and the social construction of nuclear identities in the context of the 2014 Scottish-independence referendum and the 2015 general election.